Integrative study of phytochemicals for anti-fibroid agent: A perspective on protein networks, molecular docking, ADMET, simulation, DFT and bioactivity - Christopher Busayo Olowosoke; Chioma Joy Eze; Aqsa Munir; Olusola Olatunde Dada; Kehinde Esther Omolabake; Grace Ayomide Oke; Nouh Mounadi; Samir Chtita; Tope Abraham Ibisanmi (Chemical Physics Impact, 2024)
Purpose: Beyond the pains of pregnancy, miscarriages and other child-bearing risks associated with the pride of motherhood, Uterine fibroids (UFs) are another significant reproductive age detriment in women's health. These tumours are often challenging to detect in the early stage until they become large outgrowth which always requires surgical removal to mitigate risks. However, with the understanding of alteration in the complex signalling pathways, specific protein targets in UFs pathogenesis have been identified, and this study is directed to evaluate selected dietary phytochemicals for the remedy. Methods: Consequently, this computer-aided quantum study explores thirty-one phytochemicals for anti-fibroid agents through investigation of density functional theory, molecular docking, mechanics’ free energy, absorption, distribution, metabolism, elimination, toxicity, dynamic simulation and bioactivity properties towards some selected targets. Results: From the study, the gene-disease association revealed an evidence index between 0 and 1 for six reproductive conditions including UFs. The molecular docking shows capsaicin, epigallocatechin gallate, genistein, naringin and quercetin to interact with yes-associated protein 1 (-10.019 kcal/mol), insulin-like growth factor 1 (-14.224 kcal/mol), oestrogen receptor protein (-10.152 kcal/mol), epidermal growth factor receptor protein (-11.016 kcal/mol) and progesterone receptor (-12.462 kcal/mol), with highest affinity respectively. These interaction findings correlate with the molecular mechanics’ free energy combined with generalized born and surface area affinity obtained in the regression line of the dietary phytochemicals to the mapped proteins’ active site. In addition, 50 % of the phytochemicals, plus best-docked candidates exhibit good physicochemical, satisfy drug-likeness rules and medicinal chemistry as compared to the standard drugs and co-ligands. Hence, their bioactivity supports anti-cancer potential with a good Pa>Pi ratio, and with less electronic reactivity and stable interaction from the quantum mechanical calculation and simulation at 100 ns. Conclusion: Ultimately, these phytochemicals are proposed for further experimental evaluation for efficacy in managing and treating UFs.